Multi-criteria decision analysis for responsible management of marine protected area in Semporna Sabah - Nair, Madhavan; Ramachandran, Sridar; Shuib, Ahmad; Mohammad Afandi, Syamsul Herman (Institut Kajian Dasar Pertanian dan Makanan, Universiti Putra Malaysia, 2015)
Marine Protected Area (MPA) has always been seen as a tool to save marine ecosystems that are in danger of being over exploited. Management of MPA has always been centered to ecological protection but human elements are increasingly being considered in the challenges of managing a MPA. Without the necessary structures in place, many MPA have become merely paper parks. Semporna Sabah has the most valuable MPA in the east coast of Sabah. The MPA in Semporna were gazetted for the very same reason. However, with the existence of community living within the marine park, management of the MPA requires approaches that are not conventional. The problems faced are multi facet and requires the marine park management to look at multiple criteria in their decision making process. The aim of this study is to present some of the findings gathered from various stakeholders on criterions that are essential in the decision making process to manage the marine park responsibly. A Delphi approach was used to gather the data using a three-step approach. A total of 93 decision-making criterions were identified. The shortcomings of MPA management could be addressed by analyzing the important management criteria using a decision hierarchy.